Editorial Introduction - Gordon Wells (Networks: An Online Journal for Teacher Research, 2001)
In this issue of Networks, there are articles by both classroom teachers and university-based practitioners. All are, in one way or another, concerned with the critical role of dialogue and discussion in effective learning and teaching. The issue concludes with the continuation of the exploration of the ethics of practitioner research that was introduced in the contribution to the previous issue by Jane Zeni.